2007
DOI: 10.1080/02699050701559186
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of word deafness due to auditory analysis disorder

Abstract: In a case of word deafness, this study demonstrates not only the efficacy of a specific phoneme processing therapy but also its efficacy in the improvement of higher level of cognitive treatment such as oral comprehension and its transfer in daily life. The role of errorless therapy using systematic visual cues and difficulty hierarchy must be underlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…In line with this, the other positive studies showed gains on assessments with untreated words (e.g. Morris et al,1996;Tessier et al, 2007).…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…In line with this, the other positive studies showed gains on assessments with untreated words (e.g. Morris et al,1996;Tessier et al, 2007).…”
Section: Introductionsupporting
confidence: 71%
“…These studies produced some evidence that therapy can improve discrimination skills, with four reporting gains on minimal pair tasks (Hessler & Stadie, 2008;Morris et al, 1996;Tessier et al, 2007;Grayson et al, 1997). However, in two of the studies associated gains in auditory comprehension were either not reported (Hessler & Stadie, 2008) or absent (Morris et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Implementation of language-related training activities 9 with a high cognitive and linguistic load 10 or even simply listening to music or audiotapes 11 after stroke may lead to broad functional improvements in communication, but improvements may not generalize to untrained auditory stimuli or cognitive tasks. 12,13 Moreover, everyday life communication is more demanding than laboratory tests. 14 Thus, as well as identifying auditory processing deficits after stroke, there is a need to assess the patientreported difficulties in a range of everyday life situations, including persistent nonspeech-based difficulties with recognition and localization of sounds.…”
mentioning
confidence: 99%